2020
DOI: 10.1007/s11192-020-03557-8
|View full text |Cite
|
Sign up to set email alerts
|

Open access effect on uncitedness: a large-scale study controlling by discipline, source type and visibility

Abstract: There are many factors that affect the probability of being uncited during the first years after publication. In this study, we analyze three of these factors for journals, conference proceedings and book series: the field (in 316 subject categories of the Scopus database), the access modality (open access vs. paywalled), and the visibility of the source (through the percentile of the average impact in the subject category). We quantify the effect of these factors on the probability of being uncited. This prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Many research articles in this study have not been cited or have not received any attention in social media (compiled in the database after four years). This is something that is observed frequently in the literature [32].…”
Section: Discussionsupporting
confidence: 66%
“…Many research articles in this study have not been cited or have not received any attention in social media (compiled in the database after four years). This is something that is observed frequently in the literature [32].…”
Section: Discussionsupporting
confidence: 66%
“…As indicated, many of the research articles in this study have not been cited or have not received any attention in social media (compiled in the database after four years). This is something that happens frequently in the literature in the case of the citations (Dorta-González et al. , 2020).…”
Section: Resultsmentioning
confidence: 88%
“…For example, a recent analysis of citations among OA and paywalled journal articles found that there is no general OA citation advantage and that article access status accounts for little of the variability in the number of citations an article receives (Basson, 2019). Instead, confounding factors including the reputation of the journal, the language the journal is published in, and the first author's home institution can have a stronger effect on the number of citations an article receives (Basson, 2019;Dorta-González et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%